Metal-Free Directed C–H Borylation of Indoles at the Sterically Congested C2 Position - Jiang, Wang; Bai, Jingyi; Lv, Jiahang; Zhao, Yue; Yan, Chaoguo; Shi, Zhuangzhi (Synlett, 2023)
During the past few decades, transition metal-catalyzed C–H borylation has been one of the most notable advances in synthetic chemistry and has been widely employed in the preparation of organoboron reagents. Due to economic and heavy-metal-residue concerns, there is significant interest in the development of metal-free processes to mimic metallic systems. Here, we disclose a highly efficient metal-free approach for the directed C–H borylation of C3-substituted indoles at the sterically congested C2 position that uses the inexpensive boron reagent BBr3. Compared with the conventional methods using transition metals, this practical protocol provides an ideal pathway to obtain numerous C2-borylated indoles. The benefit of the synthesis of complex molecules and their applicability to medicinal chemistry is also shown through the construction of key intermediates of (–)-goniomitine and bazedoxifene and by a total synthesis of the drug fluvastatin. Mechanistic experiments demonstrate the site selectivity of this C–H borylation process.
Keywords: C–H bond activation; borylation; indoles; BBr3; site selectivity; metal-free reaction